2004
DOI: 10.1095/biolreprod.104.028639
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Regulated Gene Expression in Bovine Blastocysts1

Abstract: Oxygen concentrations used during in vitro embryo culture can influence embryo development, cell numbers, and gene expression. Here we propose that the preimplantation bovine embryo possesses a molecular mechanism for the detection of, and response to, oxygen, mediated by a family of basic helix-loop-helix transcription factors, the hypoxia-inducible factors (HIFs). Day 5 compacting bovine embryos were cultured under different oxygen tensions (2%, 7%, 20%) and the effect on the expression of oxygen-regulated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(72 citation statements)
references
References 62 publications
6
65
0
1
Order By: Relevance
“…High oxygen tension increases H 2 O 2 production, DNA fragmentation and apoptosis, and thereby decreases the percentage of IVC embryos reaching the blastocyst stage (Van Soom et al 2002, Kitagawa et al 2004. By affecting oxidative homeostasis, it might actually decrease energy production by the mitochondria (Harvey et al 2004a). Uncouplers and inhibitors of OXPHOS appear to affect embryo development in a similar manner (Thompson et al 2000, Machaty et al 2001 as well as the expression of redox-sensitive genes such as HIF1A and HIF2A (Harvey et al 2004b).…”
Section: Response To Oxidative Stressmentioning
confidence: 99%
“…High oxygen tension increases H 2 O 2 production, DNA fragmentation and apoptosis, and thereby decreases the percentage of IVC embryos reaching the blastocyst stage (Van Soom et al 2002, Kitagawa et al 2004. By affecting oxidative homeostasis, it might actually decrease energy production by the mitochondria (Harvey et al 2004a). Uncouplers and inhibitors of OXPHOS appear to affect embryo development in a similar manner (Thompson et al 2000, Machaty et al 2001 as well as the expression of redox-sensitive genes such as HIF1A and HIF2A (Harvey et al 2004b).…”
Section: Response To Oxidative Stressmentioning
confidence: 99%
“…Recent reports have shown the differences in gene expression between the embryos developed in vivo and in vitro in mouse [56, 57,134] cow [58][59][60]. Furthermore, gene expression is highly affected by oxygen tension in in vitro condition in mouse [33,61], rabbit [62] and cow [63][64][65][66] [67]. Besides, a proteomic analysis of mouse preimplantation embryonic development has cleared that a specific pattern of proteins effectively discriminated in vitro embryos cultured under low O 2 (5%) from in vitro embryos cultured at high O 2 [68].…”
Section: Oxidative Stress and Gene Expression In Preimplantation Embryosmentioning
confidence: 99%
“…Oxidative stress to embryos cultured in vitro under ambient oxygen concentration is correlated with the generation of ROS such as hydrogen peroxide [8,21] [62] and cow [63][64][65][66] embryos (Table 1). These studies have revealed the change of individual gene expression involved in metabolic pathway [59,61,63,64], apoptotic [60], pregnancy recognition [60,129] or growth factors [60,61] etc.…”
Section: Effects Of Oxidative Stress On Development Of Preimplantatiomentioning
confidence: 99%
“…Moreover, anaerobic bacteria are able to colonize the uterine lumen (15,16). Embryos are exceedingly sensitive to oxidative damage (17)(18)(19)(20)(21)(22)(23)(24), and blastocysts produced under low O 2 have significantly more inner cell mass cells than those produced under higher O 2 tensions (25). Accordingly, embryologists generally culture embryos under a low rather than high oxygen atmosphere (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%